Electronic Fetal Heart Rate Monitoring: The Future - Khangura, Taran; Chandraharan, Edwin (Current Women's Health Reviews, 2013)
Continuous electronic fetal heart rate monitoring (EFM) using a cardiotocograph (CTG) is associated with a high false positive rate of approximately 60%. Current scientific evidence does not support a significant reduction in perinatal mortality or cerebral palsy, except for a 50% reduction in neonatal convulsions. Recent scientific evidence has questioned the role of ‘peripheral’ tests of fetal wellbeing such as fetal scalp blood sampling (FBS), fetal scalp lactate and fetal pulse oximetry in reducing the false positive rate of CTG. Fetal ECG (ST-Analyzer or STAN) shows promise in reducing neonatal admissions and operative vaginal births. Computerized CTG analysis and Fetal Physiological Score (FPS) may help reduce errors associated with CTG interpretation.
Keywords: fetal scalp lactate